Experimental investigation of the effectiveness of teaching methods of the basics of scientific research - Bachiieva, L. O. (Problems of Engineer-Pedagogical Education, 2018)
The results of experimental verification of the teaching methods of the basics scientific researchare defined in the article. The essence of the implementation of the pedagogical experiment and its main goals: definition of criteria and indicators by which to assess learning outcomes; analysis of student learning outcomes according to traditional methods; exercise test the effectiveness of experimental techniques learning the basics of scientific research of future professionalsareprovided insight into. The characteristics of the criterial basis of the study: the criterion of ' research knowledge and skills, the criterion of the influence of the elements of a methodology for developing research knowledge and skills, the criterion of the influence elements method on the formation of professionally important qualities of future specialists were presented. The essence of theoretical research methods (analysis of studying methods of the basics of scientific research; compilation of information for the development of objectives, content, methods, means and forms of education) and empirical (the observation of the educational activities of students; students surveys, the implementation of comparative pedagogical experiment) areprovided insight into.